Analysis and Comparison of Forecast Methods for a Small Enterprise - Törő, Lilla; Pusztai, László (International Journal of Engineering and Management Sciences, 2020)
The application of forecasting models is an essential part of the profitable operations of every company. However, today’s small and medium sized enterprises (SMEs) does not pay enough attention to this field. This research presents a case study in which we tried to determine the sequence of a forecasting process, furthermore, determine the best applicable method to the dataset. Seven dissimilar forecasting method was applied: moving average and weighted moving averages with different periods (2-3-4 weeks), as well as exponential smoothing. The four-week-long weighted moving average served the best solution, which was tested by tracking signal as well.